Аналтэм сяська: повесть / Геннадий Мадьяров - Мадьяров Геннадий Михайлович (Удмуртия, 1994)
Экземпляры: 1 (20160414) / Инвентарный номер: 31268 / Цена: 0.50 / Сис.шифр: С(Удм) / Авт.знак: М 33 / ГРНТИ: 17.82.31 / ББК: С(Удм)